Transmembrane dynamic lipids - Devaux, Philippe F.; Herrmann, Andreas (Wiley series in protein and peptide science, 2012)
"As the building blocks of biological membranes, lipids have a very complex set of behaviors that, when defective, can be a major distributor of diseases, including cancer. As the only book to date devoted entirely to lipids in membranes, Membrane Asymmetry and Transmembrane Motion of Lipids enlists leading research groups to present up-to-date quantitative data on the formation, stability and biological consequences of the asymmetrical organization of lipids in cell membranes. With an impressive amount of data, this book explores exciting new discoveries that show promising potential for future study"--